Florida's Future State and County Policies: 2010 Elections Will Be Significant in Future Policy Choices - Rodney L. Clouser (EDIS, 2010)
FE827, a 5-page fact sheet by Rodney L. Clouser, explains why the 2010 election cycle differs from previous election cycles and notes some of the policy issues those elected in 2010 will be debating and may be legislating that will have long-term implications for the state. Includes references. Published by the UF Department of Food and Resource Economics, February 2010.